IEEEVR2020: Exploring the First Steps Toward Standalone Virtual Conferences - Ahn, Sun Joo (Grace); Levy, Laura; Eden, Allison; Won, Andrea Stevenson; MacIntyre, Blair; Johnsen, Kyle (Frontiers in Virtual Reality, 2021)
The global COVID-19 pandemic forced all large in-person events to pivot to virtual or online platforms. IEEEVR2020 coincided with rising concerns and restrictions on travel and large gatherings, becoming one of the first academic conferences to rapidly adapt its programming to a completely virtual format. The global pandemic provided an impetus to re-examine the possibility of holding social interactions in virtual worlds. This article aims to: (1) revisit the issues of virtual conferences noted in earlier studies, focusing specifically on academic conferences, (2) introduce new survey and observational data from the recent IEEEVR2020 conference, and (3) present insights and future directions for virtual conferences during and after the COVID-19 pandemic. Findings from a field observation during the conference and a post-conference survey point to complex relationships among users, media platforms selected, and social constraints during the virtual conference.